CTNI-04. ACTIVITY OF LAROTRECTINIB IN TROPOMYOSIN RECEPTOR KINASE (TRK) FUSION CANCER PATIENTS WITH CENTRAL NERVOUS SYSTEM (CNS) METASTASES. (9th November 2020) - Patel, Jyoti D; Farago, Anna F; Hong, David S; Lassen, Ulrik N; Leyvraz, Serge; Park, Keunchil; Sohal, Davendra P S; Solomon, Benjamin; Reeves, John A; Dima, Laura; Brega, Nicoletta; Drilon, Alexander
Abstract: BACKGROUND: NTRK gene fusions occur in a range of tumor types, including those with CNS metastases. Larotrectinib, a highly selective FDA- and EMA- approved TRK inhibitor, demonstrated an objective response rate (ORR) of 79% across various cancers (Hong et al. Lancet Oncol. 2020). We report data on patients with TRK fusion cancer with CNS metastases treated with larotrectinib. METHODS: Patients with solid tumors with CNS metastases at baseline harboring an NTRK gene fusion enrolled in two clinical trials (NCT02122913 and NCT02576431) were identified. Response was assessed by the investigator per RECIST v1.1. RESULTS: As of July 15, 2019, 14 patients with CNS-metastases were enrolled: lung cancer (n=7), thyroid cancer (n=4), melanoma (n=2), and non-secretory breast cancer (n=1). Median age was 53 years (range 25–76). Including all sites of disease, the ORR was 71% (95% CI 42–92%): ten patients had a partial response (PR), two had stable disease (SD), and two had progressive disease (lung and melanoma). Of the three patients with measurable intracranial disease at baseline, the best intracranial response was 1 complete response, 1 PR, and 1 SD. Median duration of response for all patients was 14.8 months (range 1.9+ to 17.4+), median progression-free survival was 9.9 months (range 1.4 to 19.3+), and median overall survival was 27.8 months (range 1.4+ to 27.8). Treatment duration ranged from 1.4 to 25.0 months; six patients continued treatment beyond progression (lasting between 0.1+ and 8.5 months). Treatment-emergent adverse events (TEAEs) were mainly Grade 1 and 2; Grade 3 TEAEs occurred in seven patients (50%), with one (myalgia) attributed to larotrectinib (7%). There were no Grade 4 TEAEs. CONCLUSIONS: Larotrectinib was highly active and well tolerated in TRK fusion cancer patients with CNS metastases. These results support testing for NTRK gene fusions across all cancers, including in patients with CNS metastases.